TRANSFORMASI HARTA WAKAF: MEWUJUDKAN KEMAKMURAN MASJID MELALUI PENDEKATAN MASLAHAH - Harahap, Taufik Hidayat (Sekolah Tinggi Ilmu Syariah Al-Hilal Sigli Aceh- Indonesia, 2024)
This study aims to understand the methods of popularizing waqf in Pidie Regency and analyze the practice of material waqf for mosque construction according to Islamic law. The research also identifies effective waqf socialization methods and explores whether construction materials such as cement and bricks can be accepted as waqf objects under Islamic law. The study was conducted at mosques in Pidie Regency, using a qualitative descriptive research method. Data collection techniques include observation, interviews, and documentation, with data analysis using a juridical-sociological approach. The results of the study show that the management of waqf assets in Pidie Regency is in accordance with Islamic principles and government regulations. However, there are still challenges related to administrative transparency and public involvement in deliberations. To improve management, training for nazir, strengthening the administrative system, and increasing government involvement in supervision are necessary. The productive use of waqf assets is expected to enhance community welfare and the prosperity of mosques, providing sustainable benefits in line with the Islamic principle of continuous charity (sadaqah jariyah).